Arrowhead agility test in elite U-19 soccer players: positional differences and relationships with other performance tests - Michailidis, Y.; Karydopoulos, C.; Kapralos, D.; Mitrotasios, M.; Ispirlidis, I.; Margonis, K.; Metaxas, T. (Trends in Sport Sciences, 2021)
Introduction. Change of direction (COD) is an important prerequisite in soccer. Therefore, a large number of tests have been developed aiming to assess the COD of athletes. The test most commonly used in soccer include the Illinois test (ICODT), the T test, the 505 test, and the Arrowhead COD test (ACODT). Aim of Study. The aim of this study was to investigate relationships between ACODT and other field tests (ICODT, 0-10 m sprint, 0-30 m sprint, countermovement jump, squat jump) in Greek elite under-19 soccer players. Comparisons were also drawn between different field positions (central defenders, side defenders, central midfielders, side midfielders, forwards). Material and Methods. Forty Greek elite male soccer players (under 19; U-19) participated in this study and were classified into the following groups: forwards, central-midfielders, side-midfielders, centraldefenders, and side-defenders. Anthropometric variables of participants (height, weight, body mass index (BMI), % body fat) and anaerobic physiological parameters (10 m and 30 m sprint, squat jump, countermovement jump, Illinois COD test, Arrowhead COD test) were measured. Results. There were no significant differences between the position groups for any of the performance tests or the anthropometric measurements. There were significant correlations between ACODT for both sides (left and right) and 0-10 m time, 0-30 m time, and ICODT time. There were no significant correlations between ACODT and any of the jump performance tests. Conclusions. The lack of differences between positional roles is in contrast with other studies that addressed professional older soccer players. This fact indicates that the specification of the training may produce differences between positional roles as the performance level of the players is increasing. Greater sprinting and acceleration speed could augment ACODT performance.